(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article explores the similarities and differences between two prominent subfields of linguistics: Contrastive Linguistics (CL) and Cognitive Linguistics (CogL). While both disciplines focus on understanding language and its structure, they adopt different theoretical frameworks and methodologies. This article delves into the key principles, research areas, and methodologies employed within CL and CogL, providing insights into how these contrasting approaches contribute to our understanding of language and cognition.